Plasmacytoid dendritic cells and type 1 interferon promote peripheral expansion of forkhead box protein 3+ regulatory T cells specific for the ubiquitous RNA-binding nuclear antigen La/Sjögren's syndrome (SS)-B. (3rd August 2016) - Pan, Z-J; Horton, C G; Lawrence, C; Farris, A D
Summary: RNA-binding nuclear antigens are a major class of self-antigen to which immune tolerance is lost in rheumatic diseases. Serological tolerance to one such antigen, La/Sjögren's syndrome (SS)-B (La), is controlled by CD4 + T cells. This study investigated peripheral tolerance to human La (hLa) by tracking the fate of hLa-specific CD4 + T cells expressing the transgenic (Tg) 3B5.8 T cell receptor (TCR) after adoptive transfer into lymphocyte-replete recipient mice expressing hLa as a neo-self-antigen. After initial antigen-specific cell division, hLa-specific donor CD4 + T cells expressed forkhead box protein 3 (FoxP3). Donor cells retrieved from hLa Tg recipients displayed impaired proliferation and secreted interleukin (IL)−10 in vitro in response to antigenic stimulation. Transfer of highly purified FoxP3-negative donor cells demonstrated that accumulation of hLa-specific regulatory T cells (Treg ) was due primarily to expansion of small numbers of donor Treg . Depletion of recipient plasmacytoid dendritic cells (pDC), but not B cells, severely hampered the accumulation of FoxP3 + donor Treg in hLa Tg recipients. Recipient pDC expressed tolerogenic markers and higher levels of co-stimulatory and co-inhibitory molecules than B cells. Adoptive transfer of hLa peptide-loaded pDC into mice lacking expression of hLa recapitulated the accumulation of hLa-specific Treg . Blockade of the type 1 interferon (IFN) receptor in hLa Tg recipients of hLa-specific T cells impaired FoxP3 + donor T cell accumulation. Therefore, peripheral expansion of Treg specific for an RNA-binding nuclear antigen is mediated by antigen-presenting pDC in a type 1 IFN-dependent manner. These results reveal a regulatory function of pDC in controlling autoreactivity to RNA-binding nuclear antigens. Graphical Abstract: